Events affecting levels of gross alpha and gross beta activities and heavy metals composition of airborne particulate samples - Liger-Pérez, Esperanza; Dueñas-Buey, Mª Concepción; Gordo Puertas, Elisa; Cañete-Hidalgo, Sergio Andrés; Cabello Ganuza, María; Pérez-Martínez, Manuel (My University, 2016)
Particulate matter (PM) pollution is a serious environmental issue mainly due to the presence of toxic substances and trace metals in the atmosphere. The association of PM with adverse health effects has been recognized for a long time. Monitoring of both PM mass and chemical composition is important for identification of the emission source, determination of compliance with the set air quality standards and establishment of effective pollution control programs. In addition, the Saharan dust events have been recognized to have a non negligible impact on the particulate matter surface concentrations recorded in Europe. The objective of this study was to analyse temporal variation in mass concentrations, gross-alpha and gross-beta activities and heavy metal components for evaluating the integrated effects of transport and meteorology on the atmospheric loadings of substances with different sources and to further examine the relationship between the occurrence of African dust outbreaks and radionuclide activity concentrations. Gross-alpha and gross-beta radioactivity measurements are of particular interest for routine monitoring purposes and allow establishing trends in radionuclide concentrations. X-ray fluorescence analysis was successfully applied for the determination of metallic elements on the aerosol filters collected.
Keywords: Aerosoles atmosféricos; Contaminación; Gross-alpha and gross-beta activitities; Heavy metals; Atmospheric aerosols